Design of mechatronic industrial systems - Onyshchenko, Serhii (DEL c.z., 2023)
Today, thanks to the wide application of the results of research on mechatronics in industry, it is possible to define industrial mechatronics as a special direction of development of this field of science. It is devoted to the analysis of problems of connection and organization of interaction of industrial electromechanical, electronic nodes, aggregates and information devices in the process of operation and direct movement of the mechatronic system in order to obtain a synergistic effect.